ATOMS: ALMA three-millimeter observations of massive star-forming regions – XVIII. On the origin and evolution of dense gas fragments in molecular shells of compact H ii regions - Zhang, Siju; Tie Liu; Ke Wang; Zavagno, Annie; Garay, Guido; Liu, Hongli; Xu, Fengwei; Liu, Xunchuan; Sanhueza, Patricio; Soam, Archana; Zhou, Jian-Wen; Li, Shanghuo; et al. (Monthly Notices of the Royal Astronomical Society, 2024)
Fragmentation and evolution for the molecular shells of the compact H ii regions are less explored compared to their evolved counterparts. We map nine compact H ii regions with a typical diameter of 0.4 pc that are surrounded by molecular shells traced by CCH. Several to a dozen dense gas fragments probed by H13CO+ are embedded in these molecular shells. These gas fragments, strongly affected by the H ii region, have a higher surface density, mass, and turbulence than those outside the shells but within the same pc-scale natal clump. These features suggest that the shells swept up by the early H ii regions can enhance the formation of massive dense structures that may host the birth of higher-mass stars. We examine the formation of fragments and find that fragmentation of the swept-up shell is unlikely to occur in these early H ii regions, by comparing the expected time scale of shell fragmentation with the age of H ii region. We propose that the appearance of gas fragments in these shells is probably the result of sweeping up pre-existing fragments into the molecular shell that has not yet fragmented. Taken together, this work provides a basis for understanding the interplay of star-forming sites with an intricate environment containing ionization feedback such as those observed in starburst regions.